A novel quality scoring system for the evaluation of individual colonoscopy: A multicenter retrospective study. Issue 1 (January 2016) - Zhan, Qiang; Xiang, Li; Zhao, Xinhua; An, Shengli; Wang, Yadong; Xu, Yangzhi; Li, Aimin; Gong, Wei; Bai, Yang; Zhang, Yali; Liu, Side
Abstract: Background and Aim: It is essential to develop a novel evaluation system for the quality of individual colonoscopy and provide guidelines on whether and when to follow up the patient after the initial colonoscopy. This study aimed to establish and validate a scoring system for the quality of individual colonoscopy in terms of the adenoma miss rate (AMR). Methods: Patients undergoing two consecutive colonoscopies within 90 days between 2009 and 2011 from different levels of hospitals in China were enrolled into this study. Potential risk factors for adenoma miss at the individual colonoscopy in a cohort of patients were evaluated in univariate and multivariate analyses. Corresponding scores for the procedure‐related factors were generated based on their weights, and a scoring system was established and then validated by correlating the system with AMR. Results: A total of 2093 patients were enrolled. Procedure‐related factors at the individual colonoscopy (including bowel preparation and imaging methods), doctor experience, retroflexion, and withdrawal time were identified to be independent risk factors, and each of these factors was scored from 0 to 3. Then, a novel scoring system for the quality of individual colonoscopy (ranging from 0 to 9) was established, which was closely correlated with the AMRs in the establishment (adjusted R 2  = 0.845) and validation databases (adjusted R 2  = 0.733). Conclusions: The developed and validated evaluation system, consisting of procedure‐related independent factors, successfully assesses the quality of individual colonoscopy in terms of AMRs.